Matter Wave Travelling Dark Solitons in a Coupled Bose-Einstein Condensate: Matter Wave Travelling Dark Solitons in a Coupled Bose-Einstein Condensate - Qadir, Muhammad Irfan; Naz , Sumreen (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
We investigate the existence and stability of matter wave travelling coupled dark solitons in two effectively one-dimensional parallel coupled Bose-Einstein condensates. The system can be described by linearly coupled Gross-Pitaevskii equations. In particular, we have examined the effects of changing the value of coupling strength between the condensates over the stability of travelling coupled dark solitons. It is found that the travelling coupled dark solitons are unstable but the instability of the solutions can be defeated by having a control on the coupling strength.